PERAN ORANG TUA DALAM MENDIDIK ANAK PEREMPUAN (Telaah Atas Pemikiran Mohammad Fauzil Adhim) - Nurkhasanah, Ika; Sholehuddin, M. Sugeng (IAIN Pekalongan, 2013)
A woman who occupies an important role and has a continuous duty, since she is as a girl for his parents, wife for her husband, a mother for her children, a grandmother for her grandchildren. In performing her role, everyone around her demands her to perform her role as quickly as possible. Therefore, a girl needs to be given sufficient knowledge and a good education, so that later she can carry out her duties well too. This study examines how ideas Mohammad Fauzil Adhim, the author who has written about marriage, family and children's education, about how the role of parents in educating girls by Mohammad Fauzil Adhim is. The purpose of this study was to determine Mohammad Fauzil Adhim thought about the steps to educate girls as well as how the characteristics of a good parent in the child's education position by Mohammad Fauzil Adhim is. This research is expected to increase the depth of knowledge and knowledge for Muslim educators, specially in educating girls, and can be used as guidance and input for parents and educators to understand the importance of educating Muslim girls from their early age associated with their role in the future. Therefore, the children's education will be more focused and as expected by their both parents.